STUDI PENENTUAN TINGGI TITIK-TITIK JARING PEMANTAU VERTIKAL CANDI BOROBUDUR DENGAN TOTAL STATION - , GITHA EKA ROSALINA, Dwi Lestari, S.T., M.E. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Trigonometric leveling is one of the methods to determine the height differences between points. This could be done by measuring vertical angle and distance using Total Station. The accuracy of this method depends on the precision of the vertical angle, distance, instrumentâs height and reflectorâs height data. This research aims to find out the impact of giving the correction to the instrument and reflector height to the precision and accuracy of the height determination using Total Station at Borobudur vertical monitoring network. Data used in this research are leveling data using Leica SPRINTER-100 of Borobudur network in 2011 and trigonometric leveling data using Nikon DTM-322 Total Station in 2012. Correction was given to instrument and reflector height data of Borobudur network in 2012, in order to have direct vertical height of the observed points. Least square adjustment with minimum constraint was done to estimate the height and the precision of each point for three different networks, the leveling network, the trigonometric network without correction of instrument and reflector height, and trigonometric network with correction applied. Comparative study of the adjustment result from the leveling and trigonometric networks was done using Fisher and student t-test with 95% level of confidence. The result of comparative study show that the precision of estimated height from trigonometric network with correction applied and the leveling network was differ significantly. The average height precision of trigonometric data with correction applied was 0,03 m and the height precision of the leveling data was 0,002 m. The correction of instrument and reflector height of 2012 Borobudur vertical network Borobudur increased the precision of the estimated point slightly (about 0,002 m), but gave significant correction to the estimated height to the level of 0,02 m. It can be concluded that the precision of height determination using Total Station in this case has not meet the leveling precision, thus further study on trigonometric leveling need to be done.